Rain attenuation of millimetre wave above 10 GHz for terrestrial links in tropical regions. Issue 8 (12th July 2018) - Shayea, Ibraheem; Abd. Rahman, Tharek; Hadri Azmi, Marwan; Arsad, Arsany
Abstract: Millimeter waves (mm‐waves) within frequency bands of 10 to 86 GHz will be used for both microwave and access link fifth‐generation (5G) systems. Thus, it is very important to investigate these bands to ensure reliability when 5G is applied in tropical regions like Malaysia in the coming few years. One of the major obstacles facing the propagation of mm‐waves in tropical regions is the rain attenuation. Rainfall results in the absorption, scattering, and diffraction of radio waves. This contributes to increased transmission losses and a reduction in the received signal levels. The effect is more severe in tropical regions that are characterized by intense heavy rainfall and large raindrop sizes. This paper provides a general overview on rain attenuation of mm‐wave bands. It highlights the nature of rain in tropical regions and its effects on the propagation of mm‐waves. It also reports the latest measurement studies focused on rain attenuation in mm‐wave frequency bands and the prediction methods used to estimate rain attenuation in mm‐waves. It contributes to the understanding of channel behavior and the characterization of mm‐wave bands during rainfall in tropical regions, especially in Malaysia. This study further strives to determine research gaps in this field as well as the future work and various propagation measurement systems that can be used to conduct real measurements and to develop prediction models for rain attenuation in mm‐waves for 5G systems. Furthermore, this paper analyzes the rain rate and rain attenuation on the basis of real measurement data conducted in Universiti Teknologi Malaysia at Skudai Campus, Malaysia. The analyzed results indicated that the rain attenuation at 38 GHz is critical and it can result in 18.4 dB/km as specific rain attenuation at 0.01% percentage of the time. Abstract : Rain attenuation at millimetre wave is critical and resulted high attenuation of specific rain attenuation at 0.01% percentage of time. The resulted attenuation can significantly degrade the communication link during a rainy period. Therefore, employing millimetre wave for 5G systems in tropical regions can only support short path lengths.